The impact of the COVID-19 pandemic on the revealed comparative advantage of industries in the Baltic States - Jolanta Droždz; Arūnas Burinskas; Viktorija Cohen (Economies, 2023)
The active spread of COVID-19 and the resulting containment measures have made it clear that both supply and demand and global production networks are facing unprecedented shocks and disruptions. Accordingly, this has resulted in an urgent need to investigate countries' competitive situation (and its changes) during a prolonged period of uncertainty. This study aims to assess the impact of the COVID-19 pandemic on the revealed comparative advantage (RCA/ Balassa index) of the Baltic states' industries. The Balassa index was calculated for nine industries in three Baltic States (Lithuania, Latvia, and Estonia). The RCA index calculations were linked to COVID-19 cases in the countries under consideration by forming a regression equation. RCA index values and their changes were evaluated by analysing data before and after the pandemic, covering the period between 2017 and 2021. This study revealed that the COVID-19 pandemic's impact on each Baltic country's competitiveness in trade with EU countries is significantly higher than in trade with third countries. The results show that Baltic states did not have a comparative advantage in trade with third countries during this time. However, Lithuania and Latvia proved to be more resilient to the consequences of the pandemic, even though industries with a low RCA were more affected. Meanwhile, in trade with EU countries, many of the Baltic states' industries appeared to have a comparative advantage, which began to decline a few years before the pandemic's start. Nevertheless, highly competitive Baltics industries showed remarkable resilience to the impact of the pandemic. However, a short-term decrease in the RCA was observed in individual cases.
Keywords: 330; competitiveness; revealed comparative advantage; Balassa index; Baltic states; COVID-19 pandemic; international trade; RCA index